God and the teaching of theology: divine pedagogy in 1 Corinthians 1-4 - Harris, Steven Edward (Reading the Scriptures, 2019)
"Theologians today are facing a crisis of identity. Are they members of the academy or the church? Is it still possible to be members of both? In God and the Teaching of Theology, Steven Harris argues a way through the impasse by encompassing both church and academy within the umbrella of the divine economy. To accomplish this, Harris uses St. Paul's description of this economy in the opening chapters of his first letter to the Corinthians. Through Paul's discussion of wisdom, the Spirit, and the apostles' role in sharing that divine wisdom, theologians of the patristic, medieval, and Reformation eras found a description of their own work as educators; they discovered that they too had roles within the same divine economy. This book thus offers a rich description of the teaching of theology as part of God's own divine pedagogy, stretching from God the teacher himself, through the nature of students and teachers of theology, to the goal of this pedagogy: human salvation in the knowledge of God. In addressing the current identity crisis of theology faculties, Harris looks backward in order to chart a way forward. His book will appeal to academic theologians, and to theological and church educators, pastors, and Christians interested in the relationship between academic study and their faith"--